The Pilates method in the rehabilitation of musculoskeletal disorders: a systematic review - Josiane Cristiane Cruz; Rafaela Liberali; Ticiane Marcondes Fonseca da Cruz; Maria Ines Artaxo Netto
Abstract Introduction: Joseph Pilates created an authentic method of physical and mental conditioning, which he called Contrology and defined as the complete coordination of body, mind and spirit. Recent studies indicate that the Pilates Method is a useful tool in rehabilitation can improve overall health, sports performance and help in the prevention and attenuation of injuries and disorders of the musculoskeletal system. Musculoskeletal disorders are prevalent and costly conditions that develop gradually, presenting a chronic course and often remain untreated. Objective: This study aimed to identify the effects of the Pilates Method in the rehabilitation of musculoskeletal disorders through a systematic review. Methods: An active search was performed in the PubMed, PEDro, Scielo and Bireme databases. A total of 24 studies were pre-selected and their methodological quality was evaluated based on the PEDro scale. Of these, 14 fulfilled the selection criteria. Results: The studies analyzed indicate that Pilates can be effective both for the treatment of conditions such as scoliosis, back pain, ankylosing spondylitis and breast cancer, and for preventing injuries in adults, elderly people and athletes. Conclusion: The high methodological variability requires that these studies be viewed with caution. It indicates the need for the performance of new studies with high methodological quality and standardization of evaluation instruments.